Relation Between Leukocyte Count and CRP (C-Reactive Protein) Levels in Typhoid Fever Patients: Hubungan Jumlah Leukosit dan Kadar CRP (C-Reactive Protein) Pada Pasien Demam Tifoid - Alda Megawati; Andika Aliviameita (Academia Open, 2021)
Typhoid fever is a systemic infectious disease characterized by the patient experiencing fever and abdominal pain due to the spread of Salmonella bacteria. Typhoid fever sufferers cause the immune system to decline which can affect changes in the number of white blood cells and in an infection, an inflammatory process occurs that produces cytokines which are the core stimulators of acute phase protein production, including C-reactive protein (C-reactive protein = CRP). This study was conducted in April 2021 with the aim of knowing the relationship between the number of leukocytes and CRP levels in typhoid fever patients at RA Basoeni Mojokerto Hospital. The design carried out in this study was a laboratory experimental, the sample needed in this study was 30 typhoid fever patients at RA Basoeni Hospital. Examination of the leukocyte count uses an automatic method with a Hematology analyzer, while CRP examination uses a semi-quantitative method. In the Spearman correlation test, it was found that there was no significant relationship between the number of leukocytes and the level of CRP p = 0.460.